Modelling desorption isotherm for durable meat products - Bauer, Josef; Richtr, Přemysl; Beňo, Filip; Tobolka, Adam; Ševčík, Rudolf (Heliyon, 2022)
The desorption isotherms of two durable meat products (sample 1 - durable fermented meat product and sample 2 - unheated durable meat product) by Dynamic Dewpoint Isotherm (DDI) at 20, 25, and 30 °C and Saturated Salt Slurry (SSS) method at 20 °C has been studied. The data acquired from these measurements for 7 models (GAB, DLP, Henderson, Chin, Smith, Oswin, Halsey) were used and statistically evaluated. Based on our collected data, the most suitable model for these types of durable meat products is the DLP model. For the DDI method, DLP model (20-30 °C) reached the R2 = 0.999, P value 3.48-4.22 of sample 1 and R2 = 0.999, P value 1.51-3.24 of sample 2. For SSS method DLP model (20 °C) reached R2 = 0.999, P value 4.23 of sample 1 and R2 = 0.998, P value 3.68 of sample 2. The most commonly used GAB model according to statistical treatment was very accurate only for the DDI method, GAB model (20-30 °C) reached R2 ≥ 0.994, P value 1.93-7.12 of sample 1 and R2 = 0.999, P value 1.76-5.54 of sample 2. In general, for DDI method for both samples have models (DLP, GAB, Halsey, Henderson, and Oswin) a P value of less than 10% for all three measured temperatures. For the SSS method, only the DLP and Henderson models are below 10% for both samples. It has been verified that the DDI method is a suitable and accurate method for measuring desorption isotherms for durable meat products.
Keywords: DDI method; Durable meat products; Sorption isotherm models; Desorption isotherm; SSS method